Evolution of physical activity habits after a context change: The case of COVID‐19 lockdown. Issue 4 (6th April 2021) - Maltagliati, Silvio; Rebar, Amanda; Fessler, Layan; Forestier, Cyril; Sarrazin, Philippe; Chalabaev, Aïna; Sander, David; Sivaramakrishnan, Hasmini; Orsholits, Dan; Boisgontier, Matthieu P.; Ntoumanis, Nikos; Gardner, Benjamin; et al.
Abstract : Objective: Habits, defined as well‐learned associations between cues and behaviours, are essential for health‐related behaviours, including physical activity (PA). Despite the sensitivity of habits to context changes, little remains known about the influence of a context change on the interplay between PA habits and behaviours. We investigated the evolution of PA habits amidst the spring COVID‐19 lockdown, a major context change. Moreover, we examined the association of PA behaviours and autonomous motivation with this evolution. Design: Three‐wave observational longitudinal design. Methods: PA habits, behaviours, and autonomous motivation were collected through online surveys in 283 French and Swiss participants. Variables were self‐reported with reference to three time‐points: before‐, mid‐, and end‐lockdown. Results: Mixed effect modelling revealed a decrease in PA habits from before‐ to mid‐lockdown, especially among individuals with strong before‐lockdown habits. Path analysis showed that before‐lockdown PA habits were not associated with mid‐lockdown PA behaviours (β = −.02, p = .837), while mid‐lockdown PA habits were positively related to end‐lockdown PA behaviours (β = .23, p = .021). Autonomous motivation was directly associated with PA habits ( p s < .001) and withto before‐ and mid‐lockdown PA behaviours ( p s < .001) (but not with end‐lockdown PA behaviours) and did not moderate the relations between PA behaviours and habits ( p s > .072). Conclusion: PA habits were altered, and their influence on PA behaviours was impeded during the COVID‐19 lockdown. Engagement in PA behaviours and autonomous motivation helped in counteracting PA habits disruption.